A Simple and Adaptive Methodology to Use a Commercial Solvent Extraction Microsystem as Screening Tool: Validation with the U-TBP Chemical System. Issue 3 (16th April 2017) - Jasmin, Jean-Philippe; Vansteene, Axel; Vercouter, Thomas; Mariet, Clarisse
ABSTRACT: The solvent extraction of a U (VI) present at several g.L −1 from the aqueous phase [HNO3 ] = 3 M to the organic one (30% TBP) involves a change of the viscosity of the two phases during the extraction process in microsystem. This shifts the position of the interface between the two phases and then affects the quality of the separation at the outlet of the microsystem. The aim of this study is to present a simple method to stabilize the quality of the separation by controlling the interface position during solvent extraction in microsystem. First, a study at low concentration is operated in order to set flow rates and contact time that allow optimal parallel flows and mass transfer. Second, the influence of the high grade concentration (up to 140 g.L −1 ) of solute on the flows and extraction yield is studied.